Current state of European bison population “Osipovichskaya” (European Bison Conservation Newsletter, 2015)
The paper presents the history and dynamic of one of Belarussian populations of European bison “Osipovichskaya”. In 1997, 15 animals were released there and present population size is equal to 308 individuals. Dynamics of size, growth rate, birth index and causes of mortality are discussed. During years 1997–2014 total number of calves born equals to 295 but only 30 individuals died or were eliminared.
Keywords: European bison; ecology; population size; growth rate; birth index